Analysis of catastrophic earthquake characteristics and countermeasures in China. Issue 1 (April 2021) - Li, Hong; Wang, Feng; Zhang, Huifeng; Cui, Na; Zhong, Puyu
Abstract: Using the 2000-2020 Chinese earthquake disaster population death data as the research object, we conducted an analysis of the characteristics and causes of earthquake disaster population death in mainland China, and put forward targeted countermeasure suggestions for earthquake disaster mitigation.